Hubungan antara Kemampuan Matematika dengan Keterampilan Pemrograman - Zulkipli, Zulkipli (Jurnal Bangkit Indonesia, 2023)
The development of computers lasted for five generations, starting from 1940 until now. Along with rapid technological developments, software innovations in certain fields must be carried out to facilitate data processing. There is a phenomenon where some Informatics Students question "Why do they as prospective programmers still have to study Mathematics Subjects". In fact, without them realizing, one of the things they need to become a good programmer is being able to think logically, by learning how to think mathematically. The problems that have been explained give rise to the idea for researchers to see the relationship (correlation) between Mathematics Ability and Programming Skills. This research is a type of quantitative research with a descriptive approach to find out how close the relationship is between Mathematics Ability and Programming Skills. The sample taken was 60 students from the Informatics Engineering and Information Systems Study Program from one of the universities in the Riau Islands who were selected using the Random Sampling technique. Data was collected using a Likert scale questionnaire, containing 19 statements regarding mathematical abilities and 10 statements regarding programming skills. The data obtained was then analyzed using the Pearson product moment correlation analysis model. Based on the research results, it was stated that there is a close relationship between Mathematics Ability and Programming Skills